"I Am Not a Hijra": Class, Respectability, and the Emergence of the "New" Transgender Woman in India. Issue 4 (August 2020) - Mount , Liz
This article examines the mutual imbrication of gender and class that shapes how some transgender women seek incorporation into social hierarchies in postcolonial India. Existing literature demonstrates an association between transgender and middle-class-status in the global South. Through an 18-month ethnographic study in Bangalore from 2009 through 2016 with transgender women, NGO (nongovernmental organization) workers and activists, as well as textual analyses of media representations, I draw on "new woman" archetypes to argue that the discourses of empowerment and respectability that impacted middle-class cisgender women in late colonial, postcolonial and liberalized India also impact how trans women narrate their struggles and newfound opportunities. Trans woman identities are often juxtaposed to the identities of hijras, a recognized (yet socially marginal) group of working-class male-assigned gender-nonconforming people. Instead of challenging stereotypes of gender nonconformity most evident in the marginalization of hijras, some transgender women are at pains to highlight their difference from hijras . These trans women are from working-class backgrounds. It is partly their similarities in class location that propel trans women's efforts to distinguish themselves from hijras . They employ the figure of the disreputable hijra to contain negative stereotypes associated with gender nonconformity, thus positioning their identities in proximity with middle-class respectable womanhood.